POLITENESS STRATEGIES USED IN “A BRILLIANT YOUNG MIND” MOVIE: A PRAGMATIC PERSPECTIVE - Yanti Kristina Sinaga; Elprinawati Purba; David Berthony Manalu (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study discusses the use of politeness strategies in the movie “A Brilliant Young Mind.” To conduct the study, the researcher formulated the following questions: What types of politeness strategies are used in the movie, and which politeness strategies are most dominant in the movie “A Brilliant Young Mind”?. The researcher used the theory proposed by Brown and Levinson (1987). Data was collected through descriptive qualitative research and document analysis, using YouTube. The subject of this research was the movie “A Brilliant Young Mind,” while the object was the four types of politeness strategies. The data collection technique was carried out by first searching for the movie title on YouTube, watching the movie, identifying and transcribing the dialogue, then analyzing it into the four types of politeness strategies. The data analysis technique used the theory proposed by Miles & Huberman (1994). The results of the data analysis show that bald on-record appeared 15 times with a percentage of 24.19%, positive politeness appeared 28 times with a percentage of 45.16%, negative politeness appeared 12 times with a percentage of 19.35%, and off-record appeared 7 times with a percentage of 11.29%. The positive politeness strategy was the most dominant type used by the characters, with the highest frequency and percentage compared to other strategies. This shows that the characters in the movie mostly used strategies that emphasized closeness, attention, and empathy to build harmonious social relationships